Postoperative residual paralysis in patients aged over 65 years old at the Post-Anesthesia Care Unit (2016)
Abstract Introduction: Few studies have been made on the incidence of residual paralysis from nondepolarizing relaxants in people over 65 years old; however, estimating the number of cases and treatment thereof are both important. Objective: To study the incidence of residual paralysis with non-depolarizing relaxants in patients over 65 years of age and discuss treatment. Methodology: Analytical observational study based on a cohort design. Results: The pre-extubation residual paralysis was estimated at 23.2% and at 9.2% at patient admission to the Recovery Suite. Pharmacological reversal showed 89.4% and 100% success rates with Neostigmine and Sugammadex respectively, with similar times at T4/T1 > 0.9. Conclusions: The incidence of pre-extubation residual paralysis was lower than the figure published worldwide. Pharmacological reversal therapies were typically highly effective.